(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the relationship between initiative and mastery motivation among university students, and what this includes by identifying the levels of each of (initiative, mastery motivation). Distributed into (15) departments with (12) humanities departments and (3) scientific departments. The total number of students in all departments of the scientific and humanities college was (3372) males and (3601) females, as the number of males from the humanities major reached (2902) and females from the specialization. The same number (2901), and the number of males in the scientific specialization was (470) and females (700). A stratified random sample of (400) male and female students was drawn, distributed according to gender, specialization, and educational level.